BUDAYA DAN PEMASARAN Tinjauan Pengaruh Budaya terhadap Perilaku Konsumen - Kussudyarsana, Kussudyarsana (Benefit: Jurnal Manajemen dan Bisnis, 2008)
This paper tried to describe the role of culture in management marketing, especiallyin the consumer behavior field. Some aspects of culture be investigated and analyzed bycombined of theorytical background in the real context. This paper also explored the level ofculture, the existence of culture value, and discussing their impact to consumer behavior.Finally, in the end of the paper, author explained the existence of ritual and their implicationto marketing strategies.